2021
DOI: 10.1371/journal.pone.0249668
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of COVID-19 patients with clinically diagnosed bacterial co-infection: A multi-center study

Abstract: Objective To understand the clinical characteristics of COVID-19 patients with clinically diagnosed bacterial co-infection (CDBC), and therefore contributing to their early identification and prognosis estimation. Method 905 COVID-19 patients from 7 different centers were enrolled. The demography data, clinical manifestations, laboratory results, and treatments were collected accordingly for further analyses. Results Around 9.5% of the enrolled COVID-19 patients were diagnosed with CDBC. Older patients or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
59
1
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 29 publications
9
59
1
9
Order By: Relevance
“…Patients with a history of cerebrovascular disease are known to be at risk for aspiration pneumonia due to micro-aspiration, impaired airway clearance, insufficient tooth hygiene, relative immobilization and ineffective expectoration due to muscle weakness. In a study by He et al patients with cardiovascular comorbidities had a higher probability of a bRTI [43]. However, evaluation of the medical history and physical examination in patients with a history of cerebrovascular disease often contribute poorly to the COVID-19 or bRTI diagnosis, which can also explain the lower threshold to start antibiotics [44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a history of cerebrovascular disease are known to be at risk for aspiration pneumonia due to micro-aspiration, impaired airway clearance, insufficient tooth hygiene, relative immobilization and ineffective expectoration due to muscle weakness. In a study by He et al patients with cardiovascular comorbidities had a higher probability of a bRTI [43]. However, evaluation of the medical history and physical examination in patients with a history of cerebrovascular disease often contribute poorly to the COVID-19 or bRTI diagnosis, which can also explain the lower threshold to start antibiotics [44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Another meta-analysis revealed that only 7.0% of hospitalized COVID-19 patients had a bacterial co-infection [ 15 ]. A recent multi-center study showed that only 86 out of 905 (9.5%) confirmed COVID-19 patients were clinically diagnosed with bacterial co-infection [ 16 ]. This implies that only a few COVID-19 patients would need antibiotics for possible bacterial pneumonia and other superimposed/co-infections [ 17 ].…”
mentioning
confidence: 99%
“…The incidence of healthcare-associated infections observed in this study was high compared to that reported in other studies, where the proportion of patients with secondary infection ranged between 5% and 30% [ 8 , 9 , 10 , 11 ], probably due to the variability of the diagnostic methods used as well as the treatments indicated. However, when these results are compared with those of studies that only evaluated patients hospitalized in the ICU, more similar results are observed, with incidences of in-hospital infections ranging between 40% and 58% [ 3 , 12 , 13 , 14 ]. This high incidence, especially in patients in the ICU, could be explained by different reasons: (a) SARS-CoV-2 virulence factors could compromise the innate immune response at several levels, resulting in increased bacterial adhesion, growth, and dissemination [ 15 ]; (b) the possible anti-inflammatory or immunosuppressive effect developed by the use of steroids and biological agents (anti-IL-6 receptor monoclonal antibodies) [ 16 ]; (c) invasive procedures cause a breakdown of the body’s first defense barrier; (d) inflammatory syndromes, hypercatabolism, and physical immobilization, typical of critical patients, predispose them to nutritional alterations, which would generate a greater risk of developing secondary infections [ 17 ].…”
Section: Discussionmentioning
confidence: 60%